Boundaries and Music Therapy Practices in Greece: A Small Qualitative Study - Maria-Christina Papadopoulou (Approaches: Music Therapy & Special Music Education, 2012)
The use of therapeutic boundaries is an essential aspect of music therapy work internationally. However, the influence of cultural and training factors on the use of boundaries has not been explored in-depth yet. This paper presents a small qualitative study, which investigates the use of boundaries in music therapy by Greek therapists, by taking into consideration how their use is influenced by their own cultural and training backgrounds. For the purposes of this study, online email interviews with three Greek music therapists working in Greece were conducted. Interpretative phenomenological analysis was used to analyse the data that was collected through the interviews. The main findings show that Greek music therapists use boundaries in their music therapy practice according to the professional European standards.However, therapists spoke of flexibility and variations in the use of boundaries to adapt to cultural differences in their own local settings and to meet individual clients’ needs.